Patch test results with the European baseline series, 2019/20—Joint European results of the ESSCA and the EBS working groups of the ESCD, and the GEIDAC. (24th June 2022) - Uter, Wolfgang; Wilkinson, S. Mark; Aerts, Olivier; Bauer, Andrea; Borrego, Leopoldo; Brans, Richard; Buhl, Timo; Dickel, Heinrich; Dugonik, Aleksandra; Filon, Francesca Larese; Garcìa, Pedro Mercader; Giménez‐Arnau, Ana; et al.
Abstract: Background: Continual analyses of patch test results with the European baseline series (EBS) serve both contact allergy surveillance and auditing the value of included allergens. Objectives: To present results of current EBS patch testing, obtained in 53 departments in 13 European countries during 2019 and 2020. Methods: Anonymised or pseudonymised individual data and partly aggregated data on demographic/clinical characteristics and patch test rest results with the EBS were prospectively collected and centrally pooled and analysed. Results: In 2019 and 2020, 22 581 patients were patch tested with the EBS. Sensitization to nickel remained most common (19.8 [19.2–20.4]% positivity [95% confidence interval]). Fragrance mix I and Myroxylon pereirae yielded very similar results with 6.80 (6.43–7.19)% and 6.62 (6.25–7.00)% positivity, respectively. Formaldehyde at 2% aq. yielded almost one percentage point more positive reactions than 1% concentration (2.49 [2.16–2.85]% vs. 1.59 [1.33–1.88]); methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) and MI alone up to around 5% positives. Among the new additions, propolis was most commonly positive (3.48 [3.16–3.82]%), followed by 2‐hydroxyethyl methacrylate (2.32 [2.0–2.68]%). Conclusion: Ongoing surveillance on the prevalence of contact sensitization contributes to an up‐to‐date baseline series containing the most frequent and/or relevant contact sensitizers for routine patch testing in Europe. Abstract : Top five from 2019 to 2020: nickel 20%, fragrance mix I 7%, Myroxylon pereirae 7%, cobalt 6% and (chloro‐)methylisothiazolinone 5%. Newcomers 2019–2022: propolis 3%, with large geographic variation, 2‐hydroxyethyl methacrylate 2%. Important to test patients with the latest, updated version of the European baseline series.